Development of Ski Learning Media on the Khulafaur Rasyidin Theme for Class V MI Students - Selvi Sri Wahyuni; Hasbi Indra; Wido Supraha (al-Afkar, Journal For Islamic Studies, 2025)
This research is motivated by the problem that the current education system in Indonesia tends to be secular, where Islamic religious studies, including Islamic Cultural History (SKI), are taught only as knowledge without integrating aspects of Islamic culture. In the context of the Independent Curriculum, the applied learning approach does not provide sufficient space for a comprehensive understanding of Islamic history and culture, especially on the theme of Khulafaur Rasyidin, which is often discussed only from the perspective of moral examples without emphasizing the aspect of culture. The purpose of this research is to design and develop learning media that can enrich students' understanding of Islamic Cultural History on the theme of Khulafaur Rasyidin with a more integrative and holistic perspective. This research utilizes the Research and Development (R&D) method by applying the ADDIE development model which includes Analysis, Design, Development, Implementation, and Evaluation. The development stage involves validation by material experts and media experts, and linguists, as well as product trials with teachers and students at Madrasah Ibtidaiyah. The results of this study indicate that the developed learning media not only improves students' understanding of the history and exemplary behavior of the Khulafaur Rasyidin, but also integrates Islamic tsaqofah values ​​​​in a comprehensive manner. The final product is a learning media that can be used as a teaching aid in SKI subjects in MI, which is able to answer the need for a more comprehensive and integrative approach to Islamic education. The learning media for Islamic History and Culture with the theme of Khulafaur Rasyidin has been tested for its feasibility through validation by experts and users. The validation of material experts showed a score of 3.71 with a percentage of 92.8%, indicating that the content meets very good standards. The validation of media experts produced a score of 3.5 with a percentage of 87.5%, indicating a good and attractive media design. The validation of language experts with a score of 3.3 and a percentage of 82.5% indicates that the language and content delivery are good, this learning media received quite positive assessments from teachers and students.